Bacterial-yeast conversion of cellulose-containing substrates into the protein feed products (Experimental biology, 2016)
Bioconversion of cellulosic raw material for animal breeding in enriched microbial protein and probiotic feed products as a way to enhance the nutritional value of forages. Tool source bioconversion of substrates is a joint solid state fermentation by two groups of microorganisms. These are bacteria of the genus Bacillus (producers of cellulolytic enzymes and antimicrobial substances), ensuring the first stage of conversion of the saccharification of raw materials. The second special yeast strains - producers of protein. Cellulose-containing raw material – wheat bran, sunflower meal and rice hulls were inculpable daily broth bacterial culture. The cultivation was carried out at a temperature of 28-300°C within 10 days. The efficiency of fermentation, i.e. the ability of 12 strains of the genus Bacillus to grow on solid cellulosic substrates was evaluated by changes in the content of cellulose (fiber), hydrolysable 80% H2SO4 and light-hydrolyzing polysaccharides (hemicelluloses),hydrolysis with 2% HCl. During the research it was found that the loss of cellulose and hemicelluloses in bran was 2-6% in the rice husk - 7-10 %, in the sunflower – 5-9%. 6 were constructed in mixed cultures, the use of which increased the effectiveness of degradation of cellulose in 2-3 times. Most active: G23 Bacillus Bacillus licheniformis+Bacillus subtilis NP-9, Bacillus pseudomycoides, S-17+Bacillus cereus NP-1, Bacillus cereus G-7 + Bacillus subtilis S-7, Bacillus Bacillus licheniformis G-7 + Bacillus cereus P-5 hydrolysable fiber solid substrates at 20 -25 %. Then, the substrate was inculpable strains of yeast belonging to genera Candida, Pichia and Assagay. The most productive strain was Pichia guilliermondii strain IS-5. This yeast is able to grow on the original substrate to 8.8×109 CFU/g within 3 days of cultivation. The use of preliminary bacterial conversion increases the growth of yeast on average by 25-30%.The obtained results demonstrate the possibility of gradual degradation of the vegetative substrate of aerobic cellulolytic bacteria of the genus Bacillus and not cellulolytic yeast Pichia guilliermondii, which use sugar, obtained by bacterial conversion of cellulose.
Keywords: sunflower meal; rice husk; Bacillus subtilis P-2; cellobiose.